Pengaruh Leader Member Exchange Terhadap Oganizational Citizenship Behaviour Perawat Di Rumah Sakit Stella Maris Makassar - Muhammad Takwa; Andi Niartiningsih; Nurul Hidayah Nur; Mene Paradilla; Nurfitriani Nurfitriani (Lembaga Pengembangan Kinerja Dosen, 2024)
The lack of OCB behavior shown by some nurses, namely, only formal tasks that can be completed optimally without being supported by behaviors that support the creation of extra performance more than expected. The low form of OCB behavior in oneself can be seen from not caring about the work of colleagues, when the work is finished, often complaining about work and hospital policies. This study aims to analyze the effect of leader member exchange on organizational citizenship behavior of nurses at the Stella Maris Hospital. This type of research is a quantitative study using an observational study with a cross sectional study design. The samples in this study were nurses at the inpatient installation of the Stella Maris Hospital in Makassar, totaling 131 respondents. The results showed that there was an effect of leader member exchange on organizational citizenship behavior for nurses. It is recommended to the hospital management to be able to make meetings and hold workshops, by providing support to their subordinates in order to create a good relationship between superiors and subordinates so that it is easier for subordinates to convey innovative ideas and can also hold trainings for employees who can help improve creativity and innovative behavior of employees.